P Pemanfaatan Teknologi Selaku Media Pembelajaran untuk Mengembangkan Kosakata Bahasa Inggris Siswa di SMPN 3 Tamban: The Utilization of Technology as Learning Media to Develop Students’ English Vocabulary at SMPN 3 Tamban - Azmy, Fikri Fuadi; Isnaniah, Isnaniah; Yuliani, Novi Dwi; Noor, Pajrian; Najmiah, Lailatun (Kayuh Baimbai: Jurnal Pengabdian Masyarakat, 2025)
Technological advances in the digital era like today have affected all areas of life, including education. This will also encourage teachers to use technology in learning activities, including for English learning. Mastery of English vocabulary is an important aspect in learning English, especially for junior high school students. Students and teachers at SMPN 3 Tamban are still very rare in using technology as a learning medium that is very useful for the teaching and learning process in English subjects. Students and teachers at SMPN 3 Tamban can take advantage of the use of technology as a learning medium to improve English vocabulary for students at SMPN 3 Tamban. One of the efforts made to provide knowledge and understanding of the role of utilizing technology as a medium for learning English is to provide an introduction and explanation of the importance of the role of utilization regarding the use of technology in learning English to students and teachers at SMPN 3 Tamban. The method used in implementing this community service activity is in the form of presentation of materials and the English learning process including the use of technology as a learning medium to improve students' English vocabulary. The results of the introduction and presentation showed an increase in knowledge about the importance of the role of utilizing technology as a medium for learning English to improve students' English vocabulary, and were followed enthusiastically and actively by students and teachers at SMPN 3 Tamban